Feasibility and Acceptability of a Culturally- and Linguistically-Adapted Smoking Cessation Text Messaging Intervention for Latino Smokers - Cartujano-Barrera, Francisco; Sanderson Cox, Lisa; Arana-Chicas, Evelyn; Ramírez, Mariana; Perales-Puchalt, Jaime; Valera, Pamela; Díaz, Francisco J.; Catley, Delwyn; Ellerbeck, Edward F.; Cupertino, Ana Paula (Frontiers in Public Health, 2020)
Objective: Assess the feasibility and acceptability of a culturally- and linguistically-adapted smoking cessation text messaging intervention for Latino smokers. Methods: Using a community-based strategy, 50 Latino smokers were recruited to participate in a smoking cessation pilot study. Participants received a 12-week text messaging intervention and were offered Nicotine Replacement Therapy (NRT) at no cost. We assessed biochemically verified abstinence at 12 weeks, text messaging interactivity with the program, NRT utilization, self-efficacy, therapeutic alliance, and satisfaction. Results: Participants were 44.8 years old on average (SD 9.80), and they were primarily male (66%) and had no health insurance (78%). Most of the participants were born in Mexico (82%) and were light smokers (1–10 CPD) (68%). All participants requested the first order of NRT, and 66% requested a refill. Participants sent an average of 39.7 text messages during the 12-week intervention (SD 82.70). At 12 weeks, 30% of participants were biochemically verified abstinent (88% follow-up rate) and working alliance mean value was 79.2 (SD 9.04). Self-efficacy mean score increased from 33.98 (SD 10.36) at baseline to 40.05 (SD 17.65) at follow-up (p = 0.04). The majority of participants (90.9%, 40/44) reported being very or extremely satisfied with the program. Conclusion: A culturally- and linguistically-adapted smoking cessation text messaging intervention for Latinos offers a promising strategy to increase the use of NRT, generated high satisfaction and frequent interactivity, significantly increased self-efficacy, produced high therapeutic alliance, and resulted in noteworthy cessation rates at the end of treatment. Additional testing as a formal randomized clinical trial is warranted.